Environmental illusions. The use of perspective in the Studiolo di Guidobaldo da Montefeltro in Gubbio (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
Created a few years after the Urbino Studiolo (1473–1476), the Gubbio Studiolo (1479–1482), also commissioned by Duke Federico da Montefeltro and now at the Metropolitan Museum in New York, differs from its predecessor in many ways, with a less public, more intimate choice of iconography, but the rooms also share a key similarity in their efforts to blur the boundaries between real and illusory spaces. In the Gubbio Studiolo, as in the Urbino Studiolo (as well as in the northern sacristy of the cathedral of Santa Maria del Fiore in Florence or in the choir of the church of Santa Maria in Organo in Verona), the wooden panels are inlaid with half–open cabinets from which symbolic objects are spilling (lectern, mazzocchio, armillary sphere, etc.) designed to break the boundaries between science and art. This iconography perfectly suited Duke Federico, a renowned expert on humanistic mathematics: it is no coincidence that the studiolo’s upper frieze, a continuum of carved and gilded letters, celebrates the art of geometry as an “adoptive mother”.